Assessment of precision in ionospheric electron density profiles retrieved by GPS radio occultations - Alexander, Pedro Manfredo (2014)
The Constellation Observing System for Meteorology Ionosphere and Climate (COSMIC) is a six satellite radio occultation mission that was launched in April 2006. The close proximity of these satellites during some months after launch provides a unique opportunity to evaluate the precision of Global Positioning System (GPS) radio occultation (RO) retrievals of ionospheric electron density from nearly collocated and simultaneous observations. RO data from 30 consecutive days during July and August 2006 are divided into ten groups in terms of daytime or nighttime and latitude. In all cases, the best precision values (about 1%) are found at the F peak height and they slightly degrade upwards. For all daytime groups, it is seen that electron density profiles above about 120 km height exhibit a substantial improvement in precision. Nighttime groups are rather diverse: in particular, the precision becomes better than 10% above different levels between 120 and 200 km height. Our overall results show that up to 100?200 km (depending on each group), the uncertainty associated with the precision is in the order of the measured electron density values. Even worse, the retrieved values tend sometimes to be negative. Although we cannot rely directly on electron density values at these altitudes, the shape of the profiles could be indicative of some ionospheric features (e.g. waves and sporadic E layers). Above 200 km, the profiles of precision are qualitatively quite independent from daytime or latitude. From all the nearly collocated pairs studied, only 49 exhibited a difference between line of sight angles of both RO at the F peak height larger than 10. After analyzing them we find no clear indications of a significant representativeness error in electron density profiles due to the spherical assumption above 120 km height. Differences in precision between setting and rising GPS RO may be attributed to the modification of the processing algorithms applied to rising cases during the initial period of the COSMIC mission.